PENGARUH ATRIBUT CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL - Kartikasari, Aristya; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2015)
The aims of this study is to examine the infuence of corporate governance attributes like board size, independent non-executive directors, family members on the board, board meetings, directors ownership, government ownership and institutional ownership on intellectual capital disclosure. Firm size, profitability, and leverage used as control variable.The population in this study consists of all listed firms in Indonesia Stock Exchange in year 2011, 2012, and 2013. Sampling method used is purposive sampling. A criterion for firm which have a high level of market capitalization. Another criteria is the firm must have complete data on implementation of corporate governance, total data of this study is 89 data. Then, there is one sample that include outlier should be excluded from samples of observation. So, the final amounts of the sample are 88 data. Multiple regression used to be analysis techniques.The empirical result of this study show that board size, board meetings, managerial ownership, government ownership and institutional ownership have positively significant influence on intellectual capital disclosure. Independent non-executive directors and family members on the board have no significant influence to intellectual capital disclosure.